(x-6)x=247

Simple and best practice solution for (x-6)x=247 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-6)x=247 equation:


Simplifying
(x + -6) * x = 247

Reorder the terms:
(-6 + x) * x = 247

Reorder the terms for easier multiplication:
x(-6 + x) = 247
(-6 * x + x * x) = 247
(-6x + x2) = 247

Solving
-6x + x2 = 247

Solving for variable 'x'.

Reorder the terms:
-247 + -6x + x2 = 247 + -247

Combine like terms: 247 + -247 = 0
-247 + -6x + x2 = 0

Factor a trinomial.
(-13 + -1x)(19 + -1x) = 0

Subproblem 1

Set the factor '(-13 + -1x)' equal to zero and attempt to solve: Simplifying -13 + -1x = 0 Solving -13 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -1x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -1x = 0 + 13 -1x = 0 + 13 Combine like terms: 0 + 13 = 13 -1x = 13 Divide each side by '-1'. x = -13 Simplifying x = -13

Subproblem 2

Set the factor '(19 + -1x)' equal to zero and attempt to solve: Simplifying 19 + -1x = 0 Solving 19 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -1x = 0 + -19 Combine like terms: 19 + -19 = 0 0 + -1x = 0 + -19 -1x = 0 + -19 Combine like terms: 0 + -19 = -19 -1x = -19 Divide each side by '-1'. x = 19 Simplifying x = 19

Solution

x = {-13, 19}

See similar equations:

| 100-50x=(10-2x)(10-2x)(4-x) | | (3x-5)+x=(-x+15)+180 | | 2x^2+14x-44=0 | | 100-50x=(10-2x)2(4-x) | | abc*de=fghjk | | 140x+90y=690550 | | x-2=-2x+13 | | y=10log(8-6t^2+t^3) | | 3(x^2-4x)=x+10 | | 2h^2-11q+9=0 | | f(x)=2bx^4+4ax^2-16+12 | | f(x)=ax^3-2bx^2+3bx-4a | | 6cosx=8sinx | | 38/5÷13/5 | | 2x+5-13=5 | | .35n=100 | | 3y=-1x-6 | | a-60=40 | | (2x+1)+(2x-1)-x=5.29150262213 | | N+.35=100 | | 4x+5=4(x-4) | | 2v^2-v-10=0 | | 3e=13 | | 2k^2+9k-11=0 | | 2u^2+9u+7=0 | | 2x+10=72 | | x:4=16 | | Z^4-27z^2+50=0 | | -(8/27)*9 | | -(2/3)^3 | | 4v^2+11v-3=0 | | 0.30x+0.15(160)=0.15(96) |

Equations solver categories